Is tourism expansion the key to economic growth in India? An aggregate-level time series analysis - Deepti Singh; Qamar Alam (Annals of Tourism Research Empirical Insights, 2024)
The paper aims to probe the tourism-economic growth nexus in the case of India. The paper incorporates a more structural view of sector-specific macroeconomic variables like central government expenditure on tourism (CGET), investment in the tourism industry (IOT), foreign tourist arrivals, and foreign tourist visits as explanatory parameters. Johansen's cointegration and error correction model results support the long-run relationship among the variables. All the independent variables are unidirectional causal on GDP except investment in tourism, which shows long-run bidirectional causality. Thus, the long-run unidirectional tourism-led growth hypothesis is supported. The empirical implications support government and private sector-based resource allocation towards tourism expansion, thereby escalating the country's economic growth.
Keywords: 330; Granger causality; India; Johansen cointegration; Time series; Tourism led economic growth; VECM model